Metode Latihan Berbantu Media Gambar: Peningkatan Budaya Hidup Bersih dan Sehat melalui Matematika Materi Unsur-Unsur Bangun Datar - Ayu Nurhidayati (Jurnal Pendidikan Madrasah, 2019)
This research aim to improve the learning activities, and achievements of the theme of the clean and healthy living mathematical content of the elements of the flat building by utilizing image media assisted training methods before and after learning. This research is a classroom action research so that the research is limited to class II MIN 4 with a total of 30 students. Data is taken through four steps, namely, planning, action, observation, and reflection. Whereas the object is the use of assisted training methods in image media can improve the activities and achievement of learning themes of clean and healthy life mathematical content of the elements of the flat building. The data source of this study is the teacher and students of class II MIN 4 Gunungkidul. Data validation techniques using triangulation techniques and data analysis techniques used are deskripstif qualitative and quantitative. From the results of this study, it can be concluded that thematic learning on the theme of clean living and healthy mathematical content of the elements of the flat building using the image media assisted training method can increase activity and learning achievement in class II MIN 4 Gunungkidul Wonosari Subdistrict, Gunungkidul District 1 semester 2018/2019 lessons.